Poor farmers and lords of the land migrations to south Antioquia, Colombia 1800-1900 (2013)
This article examines the process of colonization in the south border of the department of Antioquia and in the territories that belonged to Cauca and Tolima. The migration of poor farmers and entrepreneurial colonization that established societies to control, monopolize and exploit vacant lands, are analyzed as well as the disagreements aroused between colonists, natives and large states owners.In the Civil War environment (1840-1900), entrepreneur landowners were focused on sugar cane farming, the business of arriería or transporting goods using pack animals, the sale of cheap liquor and lastly, the production of coffee. The foundation of the department of Caldas was based on this economy.